"P(X=x)={e^{-\\lambda_1}\\lambda_1^x \\over x!}" Given that "P(X=1)=P(X=2)." Then
"{e^{-\\lambda_1}\\lambda_1^1 \\over 1!}={e^{-\\lambda_1}\\lambda_1^2 \\over 2!}, \\lambda_1>0"
"\\lambda_1=2"
"P(Y=y)={e^{-\\lambda_2}\\lambda_2^y \\over y!}" Given that "P(Y=2)=P(Y=3)." Then
"{e^{-\\lambda_2}\\lambda_2^2 \\over 2!}={e^{-\\lambda_2}\\lambda_2^3 \\over 3!}, \\lambda_2>0"
"\\lambda_2=3" For a Poisson random variable "Z,\\ Var(Z)=\\lambda." Then
"Var(X)=\\lambda_1=2, Var(Y)=\\lambda_2=3" Hence
"Var(X-2Y)=Var(X)+2^2Var(Y)="
"=2+4(3)=14" Therefore
"Var(X-2Y)=14"
Comments
Leave a comment